2021
DOI: 10.3390/w13111497
|View full text |Cite
|
Sign up to set email alerts
|

Omnivorous Carp (Carassius gibelio) Increase Eutrophication in Part by Preventing Development of Large-Bodied Zooplankton and Submerged Macrophytes

Abstract: Fish, being an important consumer in aquatic ecosystems, plays a significant role by affecting the key processes of aquatic ecosystems. Omnivorous fish consume a variety of food both from pelagic and benthic habitats and may directly or indirectly affect the plankton community as well as the lake trophic state. We conducted a 72-day outdoor experiment in mesocosms with and without Prussian carp (Carassius auratus) to evaluate the effect of this often-stocked omnivorous fish on the plankton community and water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our study also showed that tilapia increased the concentration of TSS and decreased periphyton biomass. The increased concentration of TSS also contributes to deteriorating water quality (Hansson, 1992b;Vadeboncoeur and Carpenter, 2001;Zhang et al, 2015;Razlutskij et al, 2021). The decreased abundance of periphytic algae may further benefit phytoplankton growth, lowering the competition for sediment-associated nutrients (Hansson, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that tilapia increased the concentration of TSS and decreased periphyton biomass. The increased concentration of TSS also contributes to deteriorating water quality (Hansson, 1992b;Vadeboncoeur and Carpenter, 2001;Zhang et al, 2015;Razlutskij et al, 2021). The decreased abundance of periphytic algae may further benefit phytoplankton growth, lowering the competition for sediment-associated nutrients (Hansson, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Prussian carp (C. gibelio), Razlutskij et al (2021) found no increase in nutrient concentrations in the fish presence. In fact, TP was lower in the fish treatment than in the fish-free control.…”
Section: Introductionmentioning
confidence: 93%
“…Omnivorous fish tend to increase nutrient levels in water column, phytoplankton development and water turbidity and to decrease light intensity, which results in deteriorated conditions for submerged macrophytes and benthic algae, thereby intensifying the eutrophication (Tátrai et al 1997;Jeppesen et al 2003;Schallenberg and Sorrell 2009;Mei et al 2021;Pacheco et al 2021;Razlutskij et al 2021). For example, Prussian carp (Carassius gibelio) has been found to increase planktonic algal biomass, total suspended solids (TSS) and inorganic suspended solids (ISS) and to decrease light intensity (Richardson et al 1995;Mei et al 2021;Razlutskij et al 2021), while Crucian carp (Carassius auratus) has been found to increase turbidity, decrease benthic algae biomass and enhance release of nutrients from sediment to the water column, consequently promoting phytoplankton growth (Huang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The spread of tilapia can be controlled using biological methods, i.e., by supporting other organisms, ideally endemic and other native fish species. For example, predatory fishes such as the native Silurus triostegus and Leuciscus vorax have contributed to reductions in tilapia populations (especially juvenile tilapia) in the Khuzestan Province [97,106,107]. Management practices supporting their presence in the system would help address the issue.…”
Section: Potential Origin Possible Destructive Effects and Management...mentioning
confidence: 99%